A critical review of experimental results on low temperature charge transport in carbon nanotubes based composites - Bhatia, Ravi (2018)
Owing to their low density, high aspect ratio and excellent charge transport properties, Carbon nanotubes (CNTs) are proven to be one of the best reinforcing materials in the fabrication of composite materials. CNTs dispersed in a non-conducting matrix is an interesting system for condensed matter physicists and materials scientists; CNT based composites offer an opportunity to physicists to design different experiments for fundamental studies while these composites are suitable for several technological applications that are of interest to materials scientists. In this review article, we summarize interesting experimental results on low temperature charge transport properties of composites based on multi-wall carbon nanotubes (MWCNTs) that have been reported in the past decade. In particular, we critically review different conduction mechanisms that have been identified through detailed investigations of charge transport characteristics as functions of MWCNT loading in the composites, temperature, and magnetic field.